2014
DOI: 10.1167/iovs.13-12727
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Electrospun Poly(ε-Caprolactone) Scaffold With Improved Optical Transparency and Bioactivity for Damaged Ocular Surface Reconstruction

Abstract: The hydrophilicity of the surface achieved by plasma treatment effectively enhanced the transparency and promoted the biocompatibility of scaffolds. These nanofibers may act as biological cues for endorsing ocular surface engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 25 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…Further, our findings confirm that the structural properties and architecture of the randomly deposited electrospun fibers are able to create natural ECM for cell growth and have an effect on cellular attachment and proliferation . Thus, electrospun PCL membranes alone could provide favorable growth conditions for cell survival and offer optimum nutrient and gas exchange for cell growth, even when cells have completely penetrated the scaffolds as reported by others in the case of corneal epithelial cells …”
Section: Resultssupporting
confidence: 87%
“…Further, our findings confirm that the structural properties and architecture of the randomly deposited electrospun fibers are able to create natural ECM for cell growth and have an effect on cellular attachment and proliferation . Thus, electrospun PCL membranes alone could provide favorable growth conditions for cell survival and offer optimum nutrient and gas exchange for cell growth, even when cells have completely penetrated the scaffolds as reported by others in the case of corneal epithelial cells …”
Section: Resultssupporting
confidence: 87%
“…Shweta Sharma et al electrospun PCL nanofibrous scaffold subjected to helium-oxygen (He/O 2 ) plasma treatment. The results indicated that a plasma-treated stromal equivalent can transmit 37% more light than the untreated plasma stromal equivalent [44]. Haleh Bakhshandeh et al fabricated a two-part artificial cornea as a substitute for penetrating keratoplasty in patients with corneal blindness.…”
Section: Methods Of Fabrication Of Electrospun Scaffoldsmentioning
confidence: 99%
“…Synthetic polymers, especially FDA-approved polymers, such as PLGA, PCL, and PLA (poly lactic acid), have been used in corneal tissue engineering due to their superb mechanical properties. PCL has been electrospun into nanofibrous scaffolds (Figure 1C), allowing for inoculation of limbal epithelial cells [14], human corneal epithelial cells [44], rabbit keratocytes [45] and rabbit limbal stem cells [46] on the surface of the scaffold. Studies showed that the PCL scaffold has good biocompatibility and can improve cell attachment and proliferation.…”
Section: Materials Of Electrospun Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations